Host Intrinsic and Innate Intracellular Immunity During Herpes Simplex Virus Type 1 (HSV-1) Infection - Alandijany, Thamir (Frontiers in Microbiology, 2019)
When host cells are invaded by viruses, they deploy multifaceted intracellular defense mechanisms to control infections and limit the damage they may cause. Host intracellular antiviral immunity can be classified into two main branches: (i) intrinsic immunity, an interferon (IFN)-independent antiviral response mediated by constitutively expressed cellular proteins (so-called intrinsic host restriction factors); and (ii) innate immunity, an IFN-dependent antiviral response conferred by IFN-stimulated gene (ISG) products, which are (as indicated by their name) upregulated in response to IFN secretion following the recognition of pathogen-associated molecular patterns (PAMPs) by host pattern recognition receptors (PRRs). Recent evidence has demonstrated temporal regulation and specific viral requirements for the induction of these two arms of immunity during herpes simplex virus type 1 (HSV-1) infection. Moreover, they exert differential antiviral effects to control viral replication. Although they are distinct from one another, the words “intrinsic” and “innate” have been interchangeably and/or simultaneously used in the field of virology. Hence, the aims of this review are to (1) elucidate the current knowledge about host intrinsic and innate immunity during HSV-1 infection, (2) clarify the recent advances in the understanding of their regulation and address the distinctions between them with respect to their induction requirements and effects on viral infection, and (3) highlight the key roles of the viral E3 ubiquitin ligase ICP0 in counteracting both aspects of immunity. This review emphasizes that intrinsic and innate immunity are temporally and functionally distinct arms of host intracellular immunity during HSV-1 infection; the findings are likely pertinent to other clinically important viral infections.